2010
DOI: 10.1242/dev.042564
|View full text |Cite
|
Sign up to set email alerts
|

Smed-SmB, a member of the LSm protein superfamily, is essential for chromatoid body organization and planarian stem cell proliferation

Abstract: Planarians are an ideal model system to study in vivo the dynamics of adult pluripotent stem cells. However, our knowledge of the factors necessary for regulating the ‘stemness’ of the neoblasts, the adult stem cells of planarians, is sparse. Here, we report on the characterization of the first planarian member of the LSm protein superfamily, Smed-SmB, which is expressed in stem cells and neurons in Schmidtea mediterranea. LSm proteins are highly conserved key players of the splicing machinery. Our study shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 56 publications
1
37
0
Order By: Relevance
“…Our biochemical and sequence analyses suggest that both SMEDWI-3 and Sm protein family members are methylated in planarians. Recent work has shown that both SmB and PIWI are required for neoblast function (Fernandez-Taboada et al, 2010;Palakodeti et al, 2008;Reddien et al, 2005a). Furthermore, SmB was shown to localize to planarian CBs (Fernandez-Taboada et al, 2010) and our results suggest that the same is true for sDMA-SMEDWI-3.…”
Section: Planarian Chromatoid Body Function and The Role Of Methylationsupporting
confidence: 75%
See 2 more Smart Citations
“…Our biochemical and sequence analyses suggest that both SMEDWI-3 and Sm protein family members are methylated in planarians. Recent work has shown that both SmB and PIWI are required for neoblast function (Fernandez-Taboada et al, 2010;Palakodeti et al, 2008;Reddien et al, 2005a). Furthermore, SmB was shown to localize to planarian CBs (Fernandez-Taboada et al, 2010) and our results suggest that the same is true for sDMA-SMEDWI-3.…”
Section: Planarian Chromatoid Body Function and The Role Of Methylationsupporting
confidence: 75%
“…Many studies have identified genes required for neoblast maintenance and function in planarians (Bonuccelli et al, 2010;Conte et al, 2009;Fernandez-Taboada et al, 2010;Guo et al, 2006;Oviedo and Levin, 2007;Palakodeti et al, 2008;Pearson and Sanchez Alvarado, 2010;Reddien et al, 2005a;Reddien et al, 2005b;Rouhana et al, 2010;Salvetti et al, 2005;Scimone et al, 2010;Solana et al, 2009;Tasaki et al, 2011a;Tasaki et al, 2011b). The vast majority of genes required specifically for neoblast function encode conserved factors involved in post-transcriptional regulation of gene expression (reviewed by Shibata et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Planarians used in these experiments were from a clonal strain of the S. Mediterranea BCN-10 biotype and were maintained as previously described [68]. Planarians were starved for 1 week and were 4 to 6 mm in length when used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Then, gene expression was calculated as follows. Mean Ct values were normalized to the control housekeeping gene Smed-Ef2 (CAGCCAGTAGCTTTAAGCGATG, ACTCTCAACGCTGCTGTCACTTC) (Solana et al, 2012, Forsthoefel et al, 2012, Solana et al, 2013, Fernandez-Taboada et al, 2010) and were used to calculate relative expression (Forsthoefel et al, 2012). With the exception of experiments investigating at expression kinetics, gene expression was assessed 12 hours post-infection for Smed-p38 MAP-Kinase , 6 hours post-infection for Smed-morn2, and 24 hours post-infection with bacteria for Smed-setd8-1 and Smed-PGRP-2, -1, -3, and -4 .…”
Section: Methodsmentioning
confidence: 99%